The Effectiveness of Group Guidance Services with Rational Emotive Imagery (REI) Techniques to Increase Students' Self-Confidence at Madrasah Tsanawiyah Hifzil Qur'an Foundation Islamic Center North Sumatera - Miranda, Miranda; Hasibuan, Ali Daud (Journal of Educational Sciences, 2025)
Self confidence is essential for academic success; however, many students still experience low levels of self-confidence, which hinders the development of their potential and academic achievement. This study aims to determine the effectiveness of group counseling services using the Rational Emotive Imagery (REI) technique in improving the self confidence of 8th grade students at Madrasah Tsanawiyah Hifzil Qur'an, Islamic Centre Foundation of North Sumatra, in the 2024-2025 academic year. The research method employed is quantitative with a pre-experimental one-group pretest-posttest design. The research sample consisted of 30 students selected through purposive sampling based on the criterion of having low self-confidence levels. Data were collected using a self-confidence questionnaire that had been tested for validity and reliability. The data were analyzed using a paired sample t-test. The results showed an increase in the average self-confidence score from 65,5 in the pretest to 87,75 in the posttest. Normality and homogeneity tests indicated that the data were normally distributed and homogeneous. The t-test results showed a significance value (p-value) < 0,05, indicating a significant difference between the pretest and posttest scores. Therefore, it can be concluded that group counseling services using the REI technique are effective in increasing students’ self-confidence.